2016
DOI: 10.1002/ange.201508901
|View full text |Cite
|
Sign up to set email alerts
|

A p‐Hydroxyphenacyl–Benzothiazole–Chlorambucil Conjugate as a Real‐Time‐Monitoring Drug‐Delivery System Assisted by Excited‐State Intramolecular Proton Transfer

Abstract: Among the well-known phototriggers,t he phydroxyphenacyl (pHP) group has consistently enabled the very fast, efficient, and high-conversion release of active molecules.D espite this unique behavior,t he pHP group has been ignored as ad elivery agent, particularly in the area of theranostics,b ecause of two major limitations:I ts excitation wavelength is below400 nm, and it is nonfluorescent. We have overcome these limitations by incorporating a2 -(2'-hydroxyphenyl)benzothiazole (HBT) appendage capable of rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The nitrogen-containing substituents in 107 and 108 are positioned in a way that was expected to facilitate an excited-state intramolecular proton transfer (ESIPT) that would assist in the deprotonation of the p -hydroxyl group. Specifically, it was proposed that upon excitation to the singlet excited state, an ESIPT would occur, 631 followed by a transition to a triplet excited state, allowing the reaction to proceed as shown in Scheme 27 . 631 633 The hydrophobicity of the tetraphenylethylene 617 moiety in 108 enabled the formation of organic nanoparticles 633 using a reprecipitation technique.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrogen-containing substituents in 107 and 108 are positioned in a way that was expected to facilitate an excited-state intramolecular proton transfer (ESIPT) that would assist in the deprotonation of the p -hydroxyl group. Specifically, it was proposed that upon excitation to the singlet excited state, an ESIPT would occur, 631 followed by a transition to a triplet excited state, allowing the reaction to proceed as shown in Scheme 27 . 631 633 The hydrophobicity of the tetraphenylethylene 617 moiety in 108 enabled the formation of organic nanoparticles 633 using a reprecipitation technique.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…Specifically, it was proposed that upon excitation to the singlet excited state, an ESIPT would occur, 631 followed by a transition to a triplet excited state, allowing the reaction to proceed as shown in Scheme 27 . 631 633 The hydrophobicity of the tetraphenylethylene 617 moiety in 108 enabled the formation of organic nanoparticles 633 using a reprecipitation technique. 564 Visible light-mediated photorelease (λ irr ≥ 410 nm) of a carboxylic acid 631 , 633 (chlorambucil) and a hydroxylamine 632 (an NO-donating NONOate; 634 see section 4.2 ) from 107 and 108 proceeded in high chemical yields, with the corresponding p -hydroxyphenylacetic acid derivative being the sole additional photoproduct 631 , 633 ( Scheme 28 ).…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocaged 1 presents a distinct hydrogen bonding pattern from guanosine and is an attractive tool for studying dynamics due to the rapid release of the native nucleotide following photolysis. Longer wavelength absorptivity (≥400 nm) was required to adapt this tool for single-molecule TIRF microscopy experiments, and a recent report indicated that the benzothiazole group would fulfill this requirement (23). The viability of 1 as a photocaged precursor for guanosine was established by photolyzing the nucleoside in aqueous methanol (1:1) using light-emitting diodes (395-405 nm).…”
Section: Synthesis and Validation Of A Photocaged Guanosine For Rapidmentioning
confidence: 99%
“…The group of Pradeep Singh was able to overcome these limitations by adding a 2-(2'-hydroxyphenyl) benzothiazole (HBT) core to the pHP. 39 This HBT core induces a rapid ESIPT phenomenon which can assist the deprotonation of the pHP group for a faster release, with excitation higher than 400 nm as well as a distinct fluorescence shift upon photorelease. Using this pro-fluorescent PPG, the authors were able to develop a drug release system leading to the liberation of Chlorambucil (Cbl) using light with real time monitoring of the uncaging process.…”
Section: -Bodipy Pro-fluorescent Ppgsmentioning
confidence: 99%